PENERAPAN PRINSIP-PRINSIP MUTU DAN KEAMANAN PANGAN TEMPE DI KABUPATEN LAMPUNG BARAT - Suhartono Suhartono; Ahmad Sulaeman; Budi Setiawan (Jurnal Gizi dan Pangan, 2008)
Food Law No. 7 1996 defined food security as a condition in which the fulfillment of food for the household is reflected by the availability of sufficient food both its quantity and quality, safe, evenly distributed and within reach; meanwhile, food quality is defined as the value determined base on the criteria of food safety, nutrition content and trade standard on food stuffs, catables and beverages. The purpose of this study was to analyze the application of food quality and safety principles in the production of food product i.e tempeh at small scale industry in West Lampung. A survey on 15 selected tempeh producers was carried out using a structured questionnaire. Primary and secondary data was collected in this study through interview and observation to the 15 tempeh producers. In the general, all producers had not fully implemented food safety and quality principles as outlined in the GMP guideline. Nevertheless, the tempeh quality produced in West Lampung organoleptically was good. Several issues need to be improved i.e. cleaning raw material (soy bean), using water from safe sources, washing soy bean before and after braising, controlling small animal included mouse, and maintenance and cleany the premises.